A new species of monadal coral snake of the genus Micrurus (Serpentes, Elapidae) from western Amazon - Feitosa, Darlan Tavares; Da Silva, Nelson Jorge Jr.; Pires, Matheus Godoy; Zaher, Hussam; Prudente, Ana Lúcia Da Costa (Zootaxa, 2015)
We described a new species of monadal coral snake of the genus Micrurus from the region of Tabatinga and Leticia, along the boundaries of Brazil, Colombia, and Peru. The new species can be distinguished from the other congeners by the combination of the following characters: absence of a pale nuchal collar; black cephalic-cap extending from rostral to firstdorsal scale and enclosing white tipped prefrontal scales; upper half of first to four supralabials and postoculars black; tricolor body coloration, with 27–31 black rings bordered by narrower white rings and 27–31 red rings; tail coloration similar to body, with alternating black rings bordered by irregular narrow white rings, red rings of the same width as the black rings; ventral scales 205–225; subcaudal scales 39–47.